Peran Guru BK Dalam Melaksanakan Manajemen Bimbingan dan Konseling di Sekolah - Huda, Muhammad Nur; Syahputri, Viny; Aryadi, Sri Puspita Della; Faizah, Yusra; Murni, Sheila Natasya; Nasution, Inom (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to find out the role of Guidance and Counseling teachers in implementing Guidance and Counseling management in schools. This type of research is qualitative descriptive research with the research subject being one of the schools in the city of Medan which was determined using Random Sampling techniques. The data collection instrument uses interview guidelines supported by observation activities. The results of the research show that the management of Guidance and Counseling at this school is not being implemented at all, because the principal does not support Guidance and Counseling activities at school and there is no cooperation between Guidance and Counseling teachers and school staff, for example homeroom teachers, principals and subject teachers.